2022
DOI: 10.2174/1573406417666210628144849
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Chiral Rhodanine Derivatives Bearing Quinoxalinyl Imidazole Moiety as ALK5 Inhibitors

Abstract: Background: TGF-β signaling pathway inhibition is considered an effective way to prevent the development of several diseases. In the design and synthesis of TGF-β inhibitors, a rhodanine compound containing a quinoxalinyl imidazole moiety was found to have strong antimicrobial activity. Objective: The purpose of this work was to investigate the antimicrobial activity of other chiral rhodanine TGF-β inhibitors synthesized. Methods: Two series of 3-substituted-5-((5-(6-methylpyridin-2-yl)-4-(quinoxalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…21,22 In addition, the triazolyl group has been successfully applied in the development of selinexor (15), letrozole (16), and talzenna (17). 23,24 Furan and thiophene were used to develop tykerb (18) and orgovyx (19). 25,26 These drugs can be used effectively in cancer treatment (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 In addition, the triazolyl group has been successfully applied in the development of selinexor (15), letrozole (16), and talzenna (17). 23,24 Furan and thiophene were used to develop tykerb (18) and orgovyx (19). 25,26 These drugs can be used effectively in cancer treatment (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cinnamic acid, 14,15 pyridine/furan 16,17 and triazolyl moieties have been considered common structures in the design of anticancer drugs due to their dipolar interaction, hydrogen bond formation ability, rigidity, and solubility. 18,19 For instance, cinnamic acid was presented in many active molecules with good efficacy, such as (−)-Englerin A (12), which has been under intensive preclinical investigation at the NCI. 20 Orelabrutinib (13) and zytiga (14) containing a pyridine moiety have been approved for listing by the FDA.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current work, we prepared a number of activin receptor-like kinae 5 (ALK5) inhibitors bearing imidazole groups, [39][40][41][42] and found that compounds [43][44][45][46] (7) bearing imidazole and imidazo[2,1-b] [1,3,4]thiadiazole moiety showed a good antifungal activity and high selectivity against Grampositive and Gram-negative bacteria. We hypothesized that the high selectivity of compound 7 may be related to the insertion of a large active group at the 5-position of the imidazo[2,1-b][1,3,4]thiadiazole moiety.…”
Section: Introductionmentioning
confidence: 99%